Mid Term Appraisal for Tenth Five Year Plan (2002-2007) Government of Mizoram - Planning Commission (Planning Commission, 2002)
The size of the Approved Tenth Plan [ 2002-07] outlay of Mizoram is fixed at Rs. 230001.00 lakhs. There is an increase of about 33.72% over the total Ninth Plan expenditure which was Rs. 171996.11 lakhs at current prices. During the 10th Five Year Plan, the following sectors of development get priority so as to ensure a better quality of life for all section of the population, especially those below the poverty line :- Agriculture & Allied Activity and Rural Development sectors get priority with particular emphasis on the various components of Pradhan Mantri Gramodaya Yojana [PMGY] and rural connectivity. Efforts were being made to connect all villages and habitations as well as agricultural fields/ gardens. Besides development of potential flat land and control of shifting cultivation received due attention. Efforts were being made to provide employment opportunity to the farmers during the lean seasons.
State Planning Board Government of Mizoram